Population Health Management in Diabetes Care: Combining Clinical Audit, Risk Stratification, and Multidisciplinary Virtual Clinics in a Community Setting to Improve Diabetes Care in a Geographically Defined Population. An Integrated Diabetes Care Pilot in the North East Locality, Oxfordshire, UK - O. Kozlowska; S. Attwood; A. Lumb; G. D. Tan; R. Rea (International Journal of Integrated Care, 2020)
Background: Disparities in diabetes care are prevalent, with significant inequalities observed in access to, and outcomes of, healthcare. A population health approach offers a solution to improve the quality of care for all with systematic ways of assessing whole population requirements and treating and monitoring sub-groups in need of additional attention. Description of the care practice: Collaborative working between primary, secondary and community care was introduced in seven primary care practices in one locality in England, UK, caring for 3560 patients with diabetes and sharing the same community and secondary specialist diabetes care providers. Three elements of the intervention included 1) clinical audit, 2) risk stratification, and 3) the multi-disciplinary virtual clinics in the community. Methods: This paper evaluates the acceptability, feasibility and short-term impact on primary care of implementing a population approach intervention using direct observations of the clinics and surveys of participating clinicians. Results and discussion: Eighteen virtual clinics across seven teams took place over six months between March and July 2017 with organisation, resources, policies, education and approximately 150 individuals discussed. The feedback from primary care was positive with growing knowledge and confidence managing people with complex diabetes in primary care. Conclusion: Taking a population health approach helped to identify groups of people in need of additional diabetes care and deliver a collaborative health intervention across traditional organisational boundaries.